Chapter Il Naviglio di Ivrea da Leonardo a oggi. Storia, tecnica e territorio - Cattaneo, Maria Vittoria (Territori, 2023)
The Naviglio di Ivrea (Turin) sketched in sheet 563r of the Atlantic Code, drew Leonardo's attention when he was working as hydraulic engineer in the nearby Milan. A research on the rich documentation available in local archives led to identify techniques and materials used to build the Naviglio, often similar to those in Leonardo's hydraulic studies and drawings, and to show both its interaction with the surrounding territories and the continuous updates in hydraulic engineering from the XV to the XIX centuries. The persisting relevance of the canal through centuries is a testament to Leonardo's ancient intuition.